Combining ability studies for yield and yield components in chilli (Capsicum annuum L.) - M. Janaki; J. Dilip Babu; L. Naram Naidu; C. Venkata Ramana; C. K. Koteswara Rao and; K. Uma Krishna (Electronic Journal of Plant Breeding, 2017)
The present investigation was carried out at Horticultural Research Station, Lam farm, Guntur, Andhra Pradesh during kharif, 2013-14 and 2014-15 to estimate the combining ability effects employing the line x tester mating design with nine lines and six testers. The analysis of variance revealed that significant differences among the parents and crosses for all the 12 characters studied. Six characters viz. fruit yield per plant, plant spread, days to 50% flowering, days to fruit maturity, number of fruits per plant and number of seeds per fruit were exhibited higher magnitude of sca variances than gca variances which revealed that non-additive gene action was played an important role in the inheritance of these trait. According to gca effects, the genotypes LCA-442, LCA-654, LCA-655, LCA-703-2 and LCA-453 found to be promising general combiners for yield and yield components. The sca effects revealed that nine crosses viz., LCA 466 x LCA 705-2, LCA 607 x LCA 703-2, LCA 355 x LCA 678, LCA 504 x LCA 705-2, LCA 446 x LCA 703-2, LCA 615 x LCA 453, LCA 442 x LCA 453, LCA 607 x G4 and LCA 654 x LCA were identified as promising hybrids for fruit yield and it’s yield component characters.